PTU-044 Variation in cell cycle markers in barrett's oesophagus in relation to circumferential and axial location. (June 2019) - Alleyne, Lance; Cheung, Danny; Rees, James; King, Dominic; Prew, Sandra; Zanetto, Ulises; Muzaffar, Suhail; Anderson, Mark; Trudgill, Nigel
Abstract : Introduction: Reflux oesophagitis and early cancer in Barrett's oesophagus (BO) have been reported to occur more frequently in the 12 to 3 o'clock position at the gastro-oesophageal junction. We analysed markers of proliferation, the cell cycle and inflammation in different circumferential and axial locations in subjects with BO to further study these observations. Methods: A prospective cohort study of adult subjects with BO undergoing endoscopic surveillance between Dec 2013 and July 2016 had quadrantic biopsies taken every 2 cm of the Barrett's segment, with the circumferential location recorded for the most distal (gastro-oesophageal junction) and proximal biopsies (where 12 o'clock correlates to the gastric lesser curve). Two histopathologists (blinded to biopsy site) reported the degree of expression of various immunohistochemical markers for each biopsy site – p53, Ki67, cyclin D1, COX-2, and p21. Chi square analysis was performed to identify any association between biopsy site location and the degree of expression of the different cell markers. Results: 112 subjects were included: mean age 62.8 (SD 12.4) years; 78% male; median Barrett's segment length C4M6, 9.1% had evidence of dysplasia (6.4% LGD, 1.8% HGD, 0.9% adenocarcinoma). Expression of Ki67 was found to be highest around the 3 o'clock position and overall was 49.6% higher in the 12-6 o'clock areas in the distal biopsies, compared to 6-12 o'clock (odds ratio 1.50 [95% CI 1.001–2.24]). A similar relationship was found with p21 expression in the 12-6 o'clock biopsies but this fell just short of statistical significance (1.82 [0.96–3.47]). There was increased expression of most markers in all circumferential locations in the distal biopsies compared to the proximal biopsies – cyclin D1 (1.74 [1.29–2.34]), COX-2 (2.03 [1.48–2.78]) and p21 (2.06 [1.16–3.68]). However, expression of Ki67 was overall higher in the proximal compared to the distal biopsies (1.75 [1.31–2.35]). Conclusions: There is evidence of increased cellular proliferation, as evidenced by Ki67 expression, in the 12-6 o'clock position at the gastro-oesophageal junction. There was also increased expression of cell cycle markers and markers of inflammation at the gastro-oesophageal junction, compared with the top of the Barrett's segment. Since these findings mirror the changes of endoscopic oesophagitis, they suggest that ongoing gastro-oesophageal reflux plays a key role in the development of dysplasia and malignancy in BO.